Exploring The Job Expectations Of The Millennial Generation Vs. Generation Z - Putri, Hanna Yustina; Meilina, Restin (Universitas Nusantara PGRI Kediri, 2025)
Research aim: Exploring the difference in job expectations between the Millennial Generation and Generation Z and their impact on workforce management. Design/Methode/Approach: A qualitative descriptive study through in-depth interviews and observations of Millennial employees, Gen Z, and company leaders. Research Finding: Millennials prioritize job stability and clear structure, while Generation Z prioritizes flexibility and personal development opportunities. Theoretical contribution/Originality: A cross-generational approach with the perspective of a company leader. Practitioner/Policy implication: Strategies for an inclusive work environment and adaptive human resource management. Research limitations: Limited participation and focus on specific geographic areas reduce the scope of generalization of results.